Trend 03/1995 - 01/2015. World Bank. Global Economic Monitor: Imports Merchandise, Customs, Price, USD, Seasonally Adjusted | Country: Iceland, 03/1995-01/2015. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 051-003-023. - World Bank (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
World Bank (2015). Global Economic Monitor: Imports Merchandise, Customs, Price, USD, Seasonally Adjusted | Country: Iceland, 03/1995-01/2015. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 051-003-023. Dataset: Shows change in import prices of merchandise (goods), cost, insurance and freight basis (c.i.f.), in United States dollars, seasonally adjusted. The data are reported by country, for low-income and middle-income countries by geographic region (ie, Economic Reporting Entity), and by country income level. The Global Economic Monitor (GEM) dataset includes economic indicators on 196 countries. Data are provided where available by country, country group, and/or reporting entity. Statistics presented include interest rates, exchange rates, equity markets, bond spreads, consumer prices, Gross Domestic Product, industrial production, and merchandise trade.The World Bank obtains this data from its own databases, the International Monetary Fund and other sources. The Bank normalizes the data to the extent possible to support country-country comparisons. Data sources and years of coverage vary across indicators. Much of the data comes from the statistical systems of World Bank member countries. The quality of the data depends on how well these national systems perform. Errata announcements are posted periodically by the World Bank at http://data.worldbank.org/about/data-updates-errata. Category: International Relations and Trade Source: World Bank Founded in 1944 as a result of the Bretton Woods Conference, the World Bank is an independent specialized agency of the United Nations that provides financial and technical assistance to developing countries in order to foster economic growth and reduce poverty. Today, the World Bank Group comprises five institutions owned by 187 member countries: the International Bank for Reconstruction and Development (IBRD), which focuses on middle-income and creditworthy poor countries; the International Development Association (IDA), which focuses on least developed countries; the International Finance Corporation (IFC); the Multilateral Guarantee Agency (MIGA); and the International Centre for the Settlement of Investment Disputes (ICSID). http://www.worldbank.org/ Subject: Prices, Imports, Merchandise, International Trade